READING COMPREHENSION OF REPORT TEXT THROUGH SCIENTIFIC APPROACH - Hasibin, Nur; Mahmud, Moh; Masruroh, Nur Lailatul (IAI Darussalam, 2022)
Reading is one of the language skills. That should be mastered by students, especially for senior High School. Objectives and development of knowledge, technology, art, and culture, and relationship with the others country. It is true that language is really necessary for education. The problem of this research is How to improve the students’ reading comprehension through scientific approach. The study aimed to improve the students’ reading comprehension through scientific approach. This research design of this study was classroom action research (CAR). This research is conducted at XI Agama 2 of MA Al-Amiriyyah Blokagung, it was known that the students had problem in reading comprehension. Based on the result of analysis of the data, can be concluded that the application of scientific approach in learning report text can improve the students’ reading comprehension. It can be shown from the result of mean score and test score have increased. The mean score in pre-cycle was 65,78 and the percentage of completeness of 37%, in cycle 1 was 69,47 and percentage of completeness of 63%, the mean score in cycle 2 was 81,05 and percentage of completeness of 100%.